If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -19 = 6x + 11 Reorder the terms: -19 + 11x = 6x + 11 Reorder the terms: -19 + 11x = 11 + 6x Solving -19 + 11x = 11 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -19 + 11x + -6x = 11 + 6x + -6x Combine like terms: 11x + -6x = 5x -19 + 5x = 11 + 6x + -6x Combine like terms: 6x + -6x = 0 -19 + 5x = 11 + 0 -19 + 5x = 11 Add '19' to each side of the equation. -19 + 19 + 5x = 11 + 19 Combine like terms: -19 + 19 = 0 0 + 5x = 11 + 19 5x = 11 + 19 Combine like terms: 11 + 19 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 2-(6-2x)=0 | | 12x-15y=80 | | 2x^4-9*x^3-4x^2-5x=0 | | x*3+x^2-8*x-8=0 | | 7y-5=3x+23 | | 4(x+1)-3(x-3)=25 | | -7x+3x^2+2=0 | | (x+4)2=81 | | 137=x+y | | 10x+12=112 | | -3x^2-2x+4=0 | | 4x+62=9x-13 | | 30-6x=3x+18 | | 10-6x=3x+18 | | =4x+15 | | -35-3x=9x+19 | | 130=2x-y | | -2(x+9)+91=13+24 | | 2(111)=d | | 7x+26=4x+77 | | 4x-6x=7 | | 34-2x=7x+21 | | -3x^2-4x+1=0 | | 3-8s=-29 | | 4x+y+x+3y=180 | | x^2-6x+9=2 | | 66x+35=25 | | (7-8)+17= | | 10x-28=4x+22 | | x^2=x+4 | | 97x+66=10 | | p(x)=-2x^2+60x-25 |